PENGEMBANGAN MODUL TEMATIK BERBASIS NILAI KARAKTER DAN HIGHER ORDER THINKING SKILLS (HOTS) - Kardiana Metha Rozhana; Ganjar Setyo Widodo (PEDAGOGIK : JURNAL PENDIDIKAN, 2020)
The purpose of this research and development is to produce character values and Higher Order Thinking Skills (HOTS)-based thematic module by using the research model of Borg & Gall, which is consisted of study preliminary, planning, development of the initial draft of product, validation test of expert, revision of validation test result, individual test, limited improvements trial results, extensive test, and refinement of the final product. The validation result of product validity is “very valid” with percentages of 90.3%. The analysis results of product implementation are 91%, which was categorized “implemented well”. The analysis results of practicality showed percentages 90%, the criteria very useful without any correction/revision. The effectiveness results showed percentages of 94% with very effective criteria. While the product attractiveness showed percentages of 97% with very attractive criteria that could be used without correction/revision.